Pengabdian Masyarakat untuk Pendampingan Ibu Nifas dengan Teknik Pijat Oketani dan Oksitosin : Meningkatkan Kualitas Menyusui di Desa Awang Bangkal Barat Wilayah Kerja Puskesmas Karang Intan 2 Kabupaten Banjar - Megawati; Januarsih; Nur Rohmah Prihatanti (Health Care : Journal of Community Service, 2025)
Community service on postpartum mother assistance using Oketani and oxytocin massage techniques was carried out in Awang Bangkal Barat Village, Karang Intan 2 Public Health Center area, Banjar Regency. This activity was based on the limited knowledge of postpartum mothers regarding massage techniques that can increase breast milk production, whereas the success of exclusive breastfeeding is crucial for infant growth and the prevention of stunting. The program was conducted through counseling, discussions, Q&A sessions, and massage practice facilitated by lecturers, midwifery students, and midwives from the public health center. Knowledge evaluation was performed using pre-test and post-test assessments. The results showed a significant increase in knowledge: the “good” category improved from 40% to 80%, while the “poor” category decreased from 30% to 0%. Beyond improved knowledge, Oketani and oxytocin massage techniques were proven effective in supporting smooth breast milk production through neuroendocrine mechanisms and improved breast tissue function. These findings emphasize that education and assistance with massage techniques for postpartum mothers serve as simple, safe, and beneficial non-pharmacological interventions to support breastfeeding success. Thus, this activity contributes to reducing the risk of exclusive breastfeeding failure and plays an important role in stunting prevention in the local community.